Uma criança com deficiência visual e múltipla: análise da comunicação e interação social - Villela, Tereza Cristina Rodrigues (2012)
The present work aims to describe and analyse communication and social interaction strategies of a female child, who was four years old in the beginning of the research, with multiple disabilities; visual impairment (congenital blindness), associated with physical disability (paraparesis), with a non-confirmed diagnosis of toxoplasmosis and citomegalovirus. The road to this identification is the playful interaction, in intervention situation, realized in conformity with the needs and initiatives of the child. Thus, the interaction becomes the way to identify signs, sometimes subtle, as forms of expression, which generally go unnoticed. The child received care in an institution which was linked to the Municipal Secretariat of Health from a medium-sized city of the State of São Paulo. Since the child feared being touched, as well as touching unknown objects, and great difficulty to communicate, the search for communicative signs was chosen. These signs expressed by the child when noticed by the interlocutor, may help the interactions and, therefore, her development. By considering the sensorial ways of perception which the people with visual impairment have, this work searches, in the last instance, subsidies to their scholar inclusion. The proposal is justified through the fact that while the visual images are enough for the immediate comprehension of the child with no visual impairment, subsidied by the sensorial integration given by sight, the child with visual impairment needs more specific contextualizations. In the beginning, a period of familiarization with the child was realized, in which the interaction with her was tried to be established, so that she would trust the researcher. To the collect of the data, individual interviews with the participant's mother were made, through means of adjustments of the "Educational Evaluation of Students with Low Vision and Multiple Disabilities in Childhood Education" instrument )developed by Bruno, 2005), to the research's objectives and to the mother's vocabulary, with the purpose of identifying aspects of the child's development, as well as her interest centers and situations which generate pleasure or discomfort to the child. afterwards, the sessions of intervention/teaching proposal were made, also aiming to identify the child's interest centers as well as communicative signs expressed by her. Transcriptions of the individual interviews with the mother and the categorization of communicative behaviors during the period of intervention which demonstrated pleasure or discomfort were made for the analysis of the data. Results point to the importance of vocalization and physical contact allied as helpers of the interaction and communication with and by the child.